Upaya Meningkatkan Keaktifan Belajar Matematika dalam Pembelajaran Daring melalui Media Game Edukasi Quizizz pada Siswa Kelas V SD Negeri 1 Bajera - Sekaryati, Ni Komang Ayu (Yayasan Pendidikan Internasional Bengkulu, 2023)
The purpose of this study was to increase students' mathematics learning activeness in online learning by applying quizizz educational game media. The sample of this study were all VSD Negeri 1 Bajera class students in the even semester of the 2020/2021 academic year, with a total of 26 people. This research was conducted in two cycles, where each cycle consisted of 4 stages, namely the planning stage, action implementation, observation / evaluation, and reflection. Students' Mathematics learning activities were obtained from student activity observation sheets filled out at the end of each cycle. At the beginning of the cycle, the average student learning activity was 68.27 with a less active category. After taking action with the quiizz educational game media, in cycle I, the average score of student learning activeness was 69.92, still in the less active category. While in cycle II it increased to 85.55 very active categories. With an increase in student activeness from the beginning of the cycle to cycle I by 10.50 or 14%, and increased again from cycle I to cycle II, namely, by 12.50 or 16%. Based on these data, there is an increase in the activeness of students learning mathematics in online learning by using quizizz educational game media.